Urocleidoides spp. (Monogenea: Dactylogyridae) from the gills of Parodon nasus (Characiformes: Parodontidae) from a Brazilian stream with descriptions of two new species - de Oliveira, Glaucya Silva; Da Silva, Reinaldo José; Vieira, Fernando Emmanuel Gonçalves; Acosta, Aline Angelina (Zootaxa, 2021)
Urocleidoides spp. are reported from the gills of 20 specimens of Parodon nasus (standard length 8.5–12 cm), from the Indiana stream, Tietê River, Upper Paraná River basin, municipality of Botucatu, São Paulo State, Brazil. Urocleoidoides tenuis and two new species were found. Urocleidoides indianensis n. sp. differs from its congeners mainly by the morphology of the vaginal sclerite that is robust, sickle-shaped, and forked at the distal end; and by the bulbous-shaped accessory piece of the male copulatory complex. Urocleidoides parodoni n. sp. resembles U. tenuis by presenting male copulatory organ with approximately 7 ½ counterclockwise rings, but differs by the morphology of the accessory piece (lobate with a small hook-like projection versus pincer-shaped), vaginal sclerite (thumb-like subterminal projection vs. presence of a distal hook), vaginal tube (conspicuously sclerotized vs. slightly sclerotized), shape of the ventral bar (bowed vs. wide V-shaped), ventral and dorsal anchors (robust base and short shaft vs. considerably less robust base and long shaft), and hooks (slender shank with a weakly sclerotized subunit at base vs. dilated shank). Sequences of the partial 28S rDNA gene of the dactylogyrids found in this study are provided. Phylogenetic analyses showed Urocledoides spp. from Parodontidae clustering together with strong support values. This study increases the number of valid Urocleidoides species to 39, and the number of species described from parodontid hosts to four.